THE EFFECTS OF READING METHOD ON THE COMPREHENSION PERFORMANCE OF THE STUDENTS - Muhammad Rochman (Journey: Journal of English Language and Pedagogy, 2019)
In this study the researcher investigated the relative effects of different reading methods on the comprehension performance of the students. The scores of participants who read three comparable passages in three ways (oral, silent and subvocalizing) were compared. Results revealed a significant difference between oral reading and subvocalization, and between oral reading and silent reading. Oral reading had the greatest effect on comprehension performance among the three reading methods examined. All groups reported that oral reading was the most preferred reading method with the majority of respondents feeling the style best supported comprehension. Feedback suggested that oral reading was preferred specifically because it helps in memorizing words and texts, concentration, and practicing and pronouncing words for real world encounters. It is recommended that second language lecturers and students use all available reading methods in order to identify which method best serves their study objectives.